Photosynthesis of Periphyton and Diffusion Process as Source of Oxygen in Rich-Riffle Upstream Waters - NIKEN TUNJUNG MURTI PRATIWI; SIGID HARIYADI; RIFKI TAJUDIN (Indonesian Society for microbiology, 2011)
Most of dissolved oxygen content in stream or river water is obtained from the process of photosynthesis and diffusion. Photosynthesis process in running water is performed by autotrophic organisms, especially community of attached micro-algae or periphytic micro-algae that live attached to stone or other substrates, while intensive diffusion process occurred as water flows. Rich riffle upstream waters are characterized by stony bottom and high current. The role of the periphyton photosynthesis result and diffusion process along the water current was examined by this research. A field experimental observation was carried out at the upstream of Cisadane River (600m asl) with two different natural light conditions, the light or exposed (24630-104240 Lux) and shadowy (11120-65300 Lux) conditions. The actual dissolved oxygen contents in the area with the two conditions are relatively similar; 7.3 (light) and 7.0 mg L-1 (shadowy). Oxygen supports were significantly different at the light and shadowy conditions, whether from diffusion process 71.71% and 79.37%, respectively, or from periphyton photosynthesis, 21.73% and 15.30%, respectively. The compositions of periphytons living in the two conditions were similar; mostly composed by group of Diatom, with the same dominant species of Thalassiothrix sp. The difference in periphyton growth was shown by its density. In the light condition, the Diatom tends to grow at higher density in comparison to the shadowy condition. The role of periphyton to support oxygen in upstream waters is light dependent. The higher the light intensity (Photosynthetic Active Radiation ranged), the higher the support of oxygen will be.